Modelling the Impacts of Government Subsidies on Total Factor Productivity: An Empirical Study - Huixiang Wu; Zhi Chen; Hua Chen; Jingjing Jiang (Discrete Dynamics in Nature and Society)
Marine industry continues to grow rapidly in China, while the contribution of the total factor productivity (TFP) to its gross output still remains very limited. Facing this issue, it is urgent to promote TFP by innovation, and Chinese government provides persistent subsidies to stimulate the innovation of relative enterprises. Taking listed companies of marine industry in Shanghai and Shenzhen Stock Markets (2007–2019) as samples, this study performed empirical tests by multiple regressions to check the effects of such subsidies on the TFP of Chinese marine industry. It was observed that, as a whole, government subsidies present positive effects on the TFP of associated companies, and subsidies beforehand yield higher promotion than subsidies afterwards. The subsidies work mainly via easing financing constraints and encouraging R&D investment of relative firms. Our results are highlighted by revealing the differential effects of government subsidies on the TFP of Chinese marine industry and their functional mechanism. It implies that, besides government subsidies, the optimization of financial market may also be helpful in promoting TFP by innovation.